1992
DOI: 10.1016/0014-5793(92)80349-l
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characteristics of a positive regulatory gene, THI2 (PHO6), of thiamin biosynthesis in Saccharomyces cerevisiae

Abstract: A rlri@lrob) mutant or Succhurorr~_w,~ ccwi.siue. dclixtivc in the expression or structural genes !'or ihiamin-repressible acid phosphatasc and enzymes involved in thiumin biosynthesis. was found to relain sufiicient thiamin transport activhy. The transport activity was repressed by thiamin in growth mrdium. WC isolated rrom a S. rcrcvisbe gcnomic library two hybrid plasmids. pTSR I and pTSRZ, containing 10.2-and ILO-kilobase (kb) DNA frirgmenls. respectively, \vhich complcmcni the 1lri-'oll,n6) mutaiion of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Similar results were obtained with the yeast S. cerevisiae (11)(12)(13). Two regulatory genes are involved in the expression of the thiamine-sensitive genes.…”
Section: Transportsupporting
confidence: 84%
“…Similar results were obtained with the yeast S. cerevisiae (11)(12)(13). Two regulatory genes are involved in the expression of the thiamine-sensitive genes.…”
Section: Transportsupporting
confidence: 84%
“…Another thiamine auxotrophic mutant carrying thi2 (pho6) (9) also showed decreased T-rAPase activity, whereas thiamine transport activity was retained in this mutant (16). A complementation test between the thi2 (pho6) mutant (K269-Sc) and the thi3 mutant (TRS3) isolated in this study was then carried out.…”
Section: Methodsmentioning
confidence: 94%
“…We have already elucidated that expression of the structural genes for T-rAPase and the enzymes involved in thiamine biosynthesis in S. cerevisiae is regulated positively by THI2 (PH06) (9), whereas expression of the genes for thiamine metabolism is controlled negatively by the intracellular thiamine pyrophosphate level (15). However, as described above, the THI2 (PH06) gene seems not to be essential for expression of the thiamine transport system (16), and therefore we have attempted to obtain a thiamine auxotrophic mutant with a defect in the thiamine transport system in order to identify a positive regulatory gene for thiamine metabolism, including thiamine transport. As expected, the mutant (TRS3) isolated in this study was auxotrophic for thiamine, with defective T-rAPase and thiamine transport activities.…”
Section: Bofmentioning
confidence: 96%
See 1 more Smart Citation
“…Evidence to support this regulation includes the finding that ΔTHI2 and ΔTHI3 mutations significantly reduce the expression levels of thiamine biosynthesis "THI" genes (i.e., THI4, THI5, THI6, PHO3, and THI80) (10)(11)(12). Further studies revealed that Thi2p contains an N-terminal Zn 2 -Cys 6 domain that binds DNA upstream of the THI genes (13) and that Thi3p harbors a motif, Gly-Asp-Gly-X 24 -27 -Asn-Asn (where X is any amino acid residue), which is an apparent TPP sensor in the regulation of THI gene expression (14).…”
mentioning
confidence: 99%